THE INFLUENCE OF SOCIAL MEDIA USE ON THE SELF-PERCEPTION AND SOCIAL RELATIONS OF TEENAGERS IN THE DIGITAL ERA - Fathurohman, Ferdi; Marzuki, Marzuki; Baharta, Ridwan (PT Altin Riset Publishing, 2023)
Objective study This study aims to determine the influence of social media use on adolescents' self-perception and social relationships in the digital era. The method used is a quantitative study with linear regression. As for the data, it was obtained through the researchers distribution of questionnaires to high school teenagers in Subang Regency and then analyzed using SPSS version 16. The result of the study, namely the deep F test, is equal to 0.000 0.05. As a result, we can conclude that variable simultaneous together influences variable Y1 and Y 2 and Based on the SPSS coefficients output table on Sig. variable X, which is equal to 0.00 < 0.05, the buffer concluded that there is an influence of variable X against variables Y1 and Y2. From this data, the research presents a comprehensive picture of the influence of social media use on teenagers' self-perception and social relationships in the digital era. Other factors, such as personality, family background, and social environment, can moderate the impact of social media on adolescent behavior and well-being.